PENGARUH INDEPENDENSI, AUDIT TENURE, SKEPTISISME PROFESIONAL DAN BEBAN KERJA TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Sang Putu Ardi Stiawan; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2022)
This study aims to determine the independence, audit tenure, professional skepticism and workload of auditors' ability to detect fraud. The population in this study were employees of the BPK RI Representative Office of the Province of Bali. The sample used in this study was the employees of the BPK RI Representative Office of the Province of Bali, as many as 40 people. The data analysis technique used in this research is the validity test, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the research results, it can be seen that independence has a significant positive effect on the ability of auditors to detect fraud, audit tenure has a significant positive effect on the ability of auditors to detect fraud, professional skepticism has a significant positive effect on the ability of auditors to detect fraud, workload has a significant negative effect on the ability of auditors to detect fraud. detect cheating